Analysis of User Acceptance of ERP System on After Sales Function Using Unified Theory of Acceptance and Use of Technology (UTAUT) Model - Andwika, Verina Risky; Witjaksono, R. Wahjoe; Azizah, Anik Hanifatul (International Journal of Advances in Data and Information Systems, 2020)
Unified Theory of Acceptance and Use of Technology (UTAUT) is a model used to describe user behavior towards the acceptance of information technology. UTAUT is a development of eight previous leading theories. UTAUT has four constructs that can be a significant direct determinant of behavioral intention and use behavioral, ie performance expectancy, effort expectancy, social influence, and facilitating conditions. This model is then used to analyze user acceptance of Enterprise Resource Planning (ERP) at PT Wijaya Toyota Dago. ERP is a system that can help companies to integrate one process with another process, in order to achieve company goals. This research will explain about the relation of factors influencing acceptance and usage of ERP by using UTAUT model. This research is an explanative research with data analysis technique using PLS (Partial Least Square). Data obtained comes from respondents who are employees of After Sales function of PT Wijaya Toyota Dago, data obtained by way of distributing the questionnaire tertuup. The sample size in this study was 37 resondents and analyzed using SPSS and SmartPLS applications. The analysis results are as follows: (1) Variable Performance Expectancy (PE) has a positive and significant influence on Behavioral Intention (BI); (2) Variable Effort Expectancy (EE) has a positive and significant influence on Behavioral Intention (BI);(3) Social Influence Variables (SI) have a positive and significant influence on Behavioral Intention (BI); (4) Variable Facilitating Conditions (FC) has a positive and significant influence on Use Behavior; (5) Social Influence (SI) variable has positive but not significant influence on Behavioral Intention (BI).